The Intensity of Khasi Production: Understanding the Challenges of Modern Agriculture System in Betel Leaf Cultivation - Choudhury, Farhana Jhuma; Haque , Md. Ashraful (Advances in Social Sciences Research Journal, 2021)
The intensive agriculture system is prominent in the mainstream production technique of Bangladesh. The paper illustrates the contests of the traditional production system of Khasi about mainstream social and economic expectations of resource use. The specific Khasi adaptation process and the patterned dependency on available environmental resources can be observed in the traditional Khasi production practices. Meanwhile, the logic on the need for intensive production has been rising in the changing socio-economic resource maximization process towards sustainability. The impact of the mainstream trends of agriculture practices on a small-scale economy has been analyzed here with the changes in labor mobility, mechanism of labor control, production cost, and hierarchy issues of the traditional production system. The research findings reflect that modernity initiatives have changed the social and natural support system in production, and changes occur in the system through the market-induced priority of development. The production process is trending towards intensive cultivation. Whether a generalized community, i.e., dependent on multiple natural yielding, diversified forest resources, and social value-oriented cultivation system, can continue the traditional living in a staple food dominated mainstream agro-economy. The study shows that intensive production is growing in the traditional production field of Khasi with modern technologies. As the ongoing production process is found segmented and capital intensive, the research suggests the community-based production behavior to defend the vulnerability of the economic capital-poor Khasis of Bangladesh.